Morphological and Genetic Diversity of Mangrove Species Ceriops tagal (Perr.) C.B. Rob. Around Java Island - Sukmarani, Dhuta; Proklamasiningsih, Elly; Susanto, Agus Hery; Ardli, Erwin Riyanto; Permadi, Jefri; Palimirmo, Flandrianto Sih (Marine Science Department Diponegoro University, 2023)
Ceriops tagal (Perr.) C.B. Rob can be found in Baluran National Park, Kepulauan Seribu National Park, Karimunjawa National Park, and Segara Anakan Cilacap in Java and its surrounding areas. These locations have different demographics and environmental conditions. Plant species found in different geographical areas have varied genetic structures and morphological traits as a result of their adaptability to their environment. The goal of this study is to evaluate the morphological and genetic differences between the four populations of C. tagal in Java and its surroundings. Internode length, leaf length, leaf width, petiole length, and leaf area were the morphological characters used. The Internal Transcribed Spacer (ITS) region is used as a molecular marker. The UPGMA dendogram was used to analyze the morphological similarity, and multidimensional unfolding analysis was used to determine which character most determined the grouping. Mega X software was used to analyze genetic variation using the neighbor-joining approach, while Arlequin 3.5 software was used to estimate genetic variation within and among populations. The results of this study showed that the population of Baluran National Park has features or is distinct from the other three populations based on morphological and genetic characters; this could be because of variations in geographic conditions, and that population diversification was aided by a combination of genetic and physical divergence, restricted gene flow, and local adaptation.